2012
DOI: 10.1136/bcr-02-2012-5846
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal metastasis from squamous cell carcinoma of oesophagus with unusual presentation

Abstract: SummaryOesophageal cancer rarely metastasis to the brain but advances in brain imaging and increasing survival of these patients has led to more detection of this condition. Although oesophageal cancer is common in the north of Iran it is less frequent in the central parts such as Yazd. Leptomeningeal metastasis is very uncommon in oesophageal cancer. This paper presents a 73-year-old man with leptomeningeal carcinomatosis from squamous cell carcinoma of oesophagus presented by hoarseness due to true vocal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…A review of previously reported cases revealed that age ranges from 39 to 68 years (mean, 44.1 years), and most cases involve males. The commonest symptoms are headache, vertigo,3 hearing loss,4 focal neurological deficit, spinal haematoma,5 lumbago, dysuria,6 seizure, vision loss7 and vocal cord paralysis 8. Squamous cell type was the commonest histological variant in previous case reports, but a recent series of seven cases revealed predominance of adenocarcinoma (77%) 9.…”
Section: Discussionmentioning
confidence: 98%
“…A review of previously reported cases revealed that age ranges from 39 to 68 years (mean, 44.1 years), and most cases involve males. The commonest symptoms are headache, vertigo,3 hearing loss,4 focal neurological deficit, spinal haematoma,5 lumbago, dysuria,6 seizure, vision loss7 and vocal cord paralysis 8. Squamous cell type was the commonest histological variant in previous case reports, but a recent series of seven cases revealed predominance of adenocarcinoma (77%) 9.…”
Section: Discussionmentioning
confidence: 98%
“…It is well known that esophageal cancer may cause distant metastasis, most frequently in the lungs, pleura, liver, peritoneum, and the adrenal gland. However, metastasis to the bones is infrequent, and skull metastasis from esophageal cancer may be extremely rare [12]. Brain metastasis secondary to esophageal carcinoma is considered to be a rare event, with a reported incidence of between 0.5 and 4.8% [345].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the United States also reported low incidence of brain metastasis in patients with esophageal cancer [51113]. Although some studies have reported esophageal cancer with brain metastasis [678], dural metastasis has been reported only 3 case in the past literature [129]. Akhavan and Navabii [1] reported a case of leptomeningeal carcinomatosis from squamous cell carcinoma of esophagus presented by hoarseness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations